1998
DOI: 10.1515/cclm.1998.007
|View full text |Cite
|
Sign up to set email alerts
|

Objectives, Design and Recruitment of a Familial and Longitudinal Cohort for Studying Gene-Environment Interactions in the Field of Cardiovascular Risk: The Stanislas Cohort

Abstract: The main objective of the Stanislas cohort is to study the role and the contribution of genetic and environmental factors to cardiovascular status. We plan: a) to describe the degree of association of a large number of cardiovascular risk indicators with cardiovascular endpoints, b) to evaluate the contribution of genetic and that of environmental factors to this association, c) to follow the evolution of these risk indicators during a period of at least ten years, d) to search for the determinants influencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 25 publications
1
92
0
4
Order By: Relevance
“…0.24433X; r = 0.987; p \ 0.0047). Steroid hormones have been reported to increase aminotransferases among OC users [48,49]. In our earlier study with triglycerides, HDL and LDL, the level of serum markers were found to be high among users [50].…”
Section: Discussionmentioning
confidence: 69%
“…0.24433X; r = 0.987; p \ 0.0047). Steroid hormones have been reported to increase aminotransferases among OC users [48,49]. In our earlier study with triglycerides, HDL and LDL, the level of serum markers were found to be high among users [50].…”
Section: Discussionmentioning
confidence: 69%
“…Subjects and data collection The studied population was a sample of the STANISLAS cohort, a longitudinal family study previously described, 23 designed to investigate factors related to cardiovascular disease. Participants were Caucasian and came from the Vosges and the South of Meurthe-et-Moselle (Eastern part of France).…”
Section: Methodsmentioning
confidence: 99%
“…During 1999-2000, 750 families attended the second checkup and 320 were randomly selected for the present study (1223 individuals). 31 In addition, individuals with aspartate aminotransferase, alanine aminotransferase, or g-glutamyl transferase activities 4200 U/l; orosomucoid or haptoglobin concentrations 43 g/l, hs-CRP 410 mg/l, cholesterol or triglyceride concentrations 410 mmol/l or glucose concentration 48 mmol/l were excluded. Participants using anti-inflammatory drugs were not excluded.…”
Section: Population Studiedmentioning
confidence: 99%